Maximizing Muscle Function in Cuff-Deficient Shoulders: A Rehabilitation Proposal for Reverse Arthroplasty. (June 2021) - Razmjou, Helen; Osnabrugge, Varda van; Anunciacion, Mark; Nunn, Andrea; Drosdowech, Darren; Roszkowski, Ania; Szafirowicz, Analia; Boljanovic, Dragana; Wainwright, Amy; Nam, Diane
Purpose: The purpose of this review is to describe the role of altered joint biomechanics in reverse shoulder arthroplasty and to propose a rehabilitation protocol for a cuff-deficient glenohumeral joint based on the current evidence. Methods and Materials: The proposed rehabilitation incorporates the principles of pertinent muscle loading while considering risk factors and surgical complications. Results: In light of altered function of shoulder muscles in reverse arthroplasty, scapular plane abduction should be more often utilized as it better activates deltoid, teres minor, upper trapezius, and serratus anterior. Given the absence of supraspinatus and infraspinatus and reduction of external rotation moment arm of the deltoid in reverse arthroplasty, significant recovery of external rotation may not occur, although an intact teres minor may assist external rotation in the elevated position. Conclusion: Improving the efficiency of deltoid function before and after reverse shoulder arthroplasty is a key factor in the rehabilitation of the cuff deficient shoulders. Performing exercises in scapular plane and higher abduction angles activates deltoid and other important muscles more efficiently and optimizes surgical outcomes.